Sustainability Engineering A Design Guide for the Chemical Process Industry - Perl, Jeffery (Springer International Publishing : Imprint: Springer, 2016)
This book explores sustainability engineering through the lens of the manufacturing and chemical process industries to elucidate the safe, and economic implementation of process designs used to transform raw materials into useful finished products. The author applies the tenets of sustainability science to develop an engineering methodology that supports the perpetual availability of raw materials through recycling/reuse/repurposing, while incorporating inexhaustible supplies, such as: solar energy, municipal waste, that encompasses the husbandry of these resources in a manner that minimizes negative environmental impacts. Anyone involved in the design or manufacturing of chemicals, or the upgrade of existing manufacturing processes, will benefit from this book's suggestions for identifying improvement options, while adding the pivotal aspect of sustainability to the usual cost and safety equation optimization elements. .